Effects of Urethritis on Human Immunodeficiency Virus (HIV) in Semen: Implications for HIV Prevention and Cure. (9th October 2020) - Chen, Jane S; Matoga, Mitch; Massa, Cecilia; Tegha, Gerald; Ndalama, Beatrice; Bonongwe, Naomi; Mathiya, Esther; Jere, Edward; Banda, Gabriel; Loftis, Amy J; Lancaster, Kathryn E; Miller, William C; et al.
Abstract: Background: Prior to the widespread availability of antiretroviral therapy (ART), men living with human immunodeficiency virus (HIV) with urethritis had increased concentrations of HIV in semen. This study aims to better evaluate HIV shedding in men with urethritis receiving ART, and its implications for the cure of HIV. Methods: Men living with HIV with urethritis taking ART ≥12 weeks were enrolled at a sexually transmitted infections clinic in Lilongwe, Malawi. Study follow-up included visits at 1, 2, 4, 8, 12, 24, 36, and 48 weeks after urethritis diagnosis and treatment. Matched blood and semen samples were collected at all visits, and all additional episodes of urethritis were followed with extra visits 1, 2, and 4 weeks after treatment. Results: There were 111 men enrolled in the study between January 2017–March 2019, and 77 (69%) were suppressed in the blood (<400 copies/mL). Among the 77 men, 87 episodes of urethritis were evaluated during follow-up. Of the 87 episodes, 15 episodes (17%) had instances of seminal viral shedding ≥400 copies/mL despite viral suppression in the blood. During nonurethritis follow-up, ≤6% of men at each visit had a viral load ≥400 copies/mL in the semen while maintaining viral suppression in the blood. Conclusions: An HIV cure requires the elimination of HIV from every body compartment, but available ART does not currently accomplish this. Our study highlights the male genital tract as a local source of HIV that can be reversibly activated. A better understanding of this phenomenon is important to advance the HIV cure field. Abstract : Urethritis increases human immunodeficiency virus (HIV) viral shedding in semen despite viral suppression in blood. After antibiotic treatment, seminal viremia decreases to baseline levels of "blipping" within 4 weeks. Understanding HIV in the genital compartment is important for HIV cure.